Evaluation of zebrafish (Danio rerio) as an animal model for the viral infections of fish. Issue 6 (28th March 2019) - Rakus, Krzysztof; Adamek, Mikołaj; Mojżesz, Miriam; Podlasz, Piotr; Chmielewska‐Krzesińska, Małgorzata; Naumowicz, Karolina; Kasica‐Jarosz, Natalia; Kłak, Katarzyna; Rakers, Sebastian; Way, Keith; Steinhagen, Dieter; Chadzińska, Magdalena
Abstract: Zebrafish ( Danio rerio ) is a laboratory model organism used in different areas of biological research including studies of immune response and host–pathogen interactions. Thanks to many biological tools available, zebrafish becomes also an important model in aquaculture research since several fish viral infection models have been developed for zebrafish. Here, we have evaluated the possible use of zebrafish to study infections with fish viruses that have not yet been tested on this model organism. In vitro studies demonstrated that chum salmon reovirus (CSV; aquareovirus A) and two alloherpesviruses cyprinid herpesvirus 1 (CyHV‐1) and cyprinid herpesvirus 3 (CyHV‐3) are able to replicate in zebrafish cell lines ZF4 and SJD.1. Moreover, CSV induced a clear cytopathic effect and up‐regulated the expression of antiviral genes vig‐1 and mxa in both cell lines. In vivo studies demonstrated that both CSV and CyHV‐3 induce up‐regulation of vig‐1 and mxa expression in kidney and spleen of adult zebrafish after infection by i.p. injection but not in larvae after infection by immersion. CyHV‐3 is eliminated quickly from fish; therefore, virus clearing process could be evaluated, and in CSV‐infected fish, a prolonged confrontation of the host with the pathogen could be studied.